An Overview on Two Valuable Natural and Bioactive Compounds, Thymol and Carvacrol, in Medicinal Plants - HA Naghdibadi; M Abdollahi; A Mehrafarin; M Ghorbanpour; SM Tolyat; A Qaderi; M Ghiaci Yekta (Institue of Medicinal Plants, ACECR, 2017)
Thymol (2-isopropyl-5-methylphenol), and carvacrol (5-isopropyl-2-methylphenol) are the main components of the essential oils of some Laminaceae,Verbenaceae and Ranunculaceae members such as oregano, thyme, savory, etc. The formation of thymol and carvacrol is thought to involve hydroxylation of γ-terpinene and p-cymene precursors. They are produced by the plant species as a chemical defense mechanism upon exposure to pathogens, pests, herbivores, or environmental stresses. Accordingly, the potent antimicrobial and fungi toxic properties of these compounds against various plant pathogens have been demonstrated. They have antibacterial, antifungal, insecticidal, and anti-oxidative properties which are the basis for the wide use of these compounds in the cosmetic, food, and pharmaceutical industries.